Biogenetic ties and parent‐child relationships: The misplaced critique. (6th August 2019) - Murphy, Timothy F.
Abstract: According to an almost axiomatic standard in bioethics, moral commitment should ground parents' relationship with their children, rather than biogenetic relatedness. This standard has been used lately to express skepticism about extending existing assisted reproductive treatments (ARTs) to same‐sex couples and to research into novel fertility interventions for those couples, but this skepticism is misplaced on several grounds. As a matter of access and equity, same‐sex couples seem presumptively entitled to genetic relatedness to their children as far as possible both in regard to existing ARTs and to novel ARTs under investigation. For those worried about the effects of trying to secure biogenetic relatedness for same‐sex couples, it may be noted that same‐sex couples will only ever be a fraction of the parents implicated in propping up "biologism, " as the expectation of biogenetic relatedness it is sometimes called. The cultural force of biologism would survive almost intact even if no same‐sex couples were ever to have genetically related children. It is therefore hard to see why same‐sex couples should forfeit aspirations to biogenetic relationships with their children or enjoy less subsidy for ARTs than the subsidy given to different‐sex couples. As matter of moral consistency, the full implications of the biologism critique have yet to be evaluated relative to different‐sex couples.